Opposition to the Affordable Care Act has Little to do with Health Care - Franz, Berkeley (Race and social problems, 2021)
The Affordable Care Act (ACA) has vastly reduced racial health insurance disparities, but efforts continue to repeal this health care law. It is not clear, however, whether this policy is rejected because of its health care provisions, or if the ACA is interpreted primarily as a social welfare policy aimed at providing resources specifically to non-white Americans. In this paper, we assess whether the racial divide in opposition to the Affordable Care Act is unique to this law or represents a reflection of a longer history of racialized social welfare policies in the U.S. The for this research come from the American National Election Studies (ANES) 2016 Time Series Study which targets United States-based citizens aged 18 and older. We conducted logistic regression to understand how racial attitudes and support for social policies relate to opposition to the ACA. Perceptions of the ACA, especially among white Americans, were related to both support for affirmative action in hiring and education and racial resentment more generally. Attitudes toward the ACA were unrelated to support for policies that have not been explicitly framed as benefitting non-white Americans. As public debates related to whether to amend the ACA or repeal and replace it altogether continue, scholars and public health practitioners should emphasize the role that racism and racial resentment more specifically play in health policy debates.